Action mechanism of different fibres on structure and property of plated coatings. (May 2015) - Jin, G.; Hou, D. D.; Li, J. Y.; Liu, Z.; Hu, Z. F.; Cui, X. F.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper tentatively chooses polyester, bamboo fibre and cotton as solution carrier during the plating process. The morphology, deposition rate, phase structure, hardness, friction and wear properties of coatings is characterised. Water absorbency, heat dissipation and electrical conductivity of three different solution carriers are analysed in order to study their action mechanism. The results show that the bamboo fibre presents the smoothest and compacts surface morphology and good water absorbency, which can ensure the supplement of solution. It also features larger electricity resistance and lower deposition rate, but fine grain, high hardness and good wear-resistance, all of which result in the best comprehensive performance. Cotton, with the best water absorbency, characterises higher hardness but poor uniformity and wear-resistance. Polyester carries the worst water absorbency, fast deposition rate, low hardness and better wear-resistance.